A prescrição nas ações de acidente de trabalho sob o enfoque da proteção à saúde do trabalhador - MEIRA, Armando Dayverson Pegado (Universidade Federal do Pará, 2017)
The prescription is an institute of legal science that imposes time limit for the holder of a subjective right to claim satisfaction of their right. It isintendedtoensure legal certainty in theprivatesphere of individualssince time is natural phenomenonthat interferes in relationsbetweenindividuals and thatmaymodifyorterminatethe legal heritage of people. However, thecollectiverelationshipsinvolvingenvironmentalissues and legal certaintytranslatesintocompliancewiththereparatory legal dutyatany time, for theenvironmentaldamageisconsideredtobemetaindividual and intergenerational. The labor accident, whichoriginates in labor relationships, causes damagetotheworkers' health and generatesthesubjectiverighttocompensation. AftertheConstitution of 1988, the Labor Courtbecamethejurisdictiontoprocess labor accidentlawsuitsfiledbyworkersagainstemployers. Fromthisjurisdictionarosethequestion as towhichstatute of limitationsshouldbeappliedtothecompensatoryclaims of workers for damagetotheirhealthresultingfromaccidentsatwork: if it shouldbethat of labor lawor civil law. However, thereis a doctrinalcurrentunderstandingthatthe labor accidentis a type of environmentalpollution, thatharmshumanwell-being, withharmfulconsequencesthat are trans-generational. Therefore, compensationclaims for thedamagescausedtoworkers' health in workplaceaccidents, isimprescriptible. In thisstudy, wewillinvestigatehowstatute of limitationsisappliedinthe legal relations of civil nature and labor nature as well as thereasonsnottoapplytheprescription in thecollectiverelationships of anenvironmentalnature. WewillalsostudyaboutwhatBrazilianlegislationunderstandsby labor accidents. It willthenbeverifiedwhattypes of damagetoworkers' health a labor accidentcan cause. Wewillalsobeanalyzingtheemployer'sliability in accidentscaused in the labor ambience. Afterthis, favorable legal arguments for thejurisdiction of the Labor Courtstojudgeimmaterialdamagesarisingfromtheworkrelationshipwillbepresented. Successively, thestudyaboutthe legal arguments for the use of limitationperiods, accordingtothe Labor Law and the Civil Law, theaction for damagesrelatedtoworkers' health in labor accidents, as well as thearguments for non-applicability of thistype of legal actionwillbeanalyzed. Finally, wewill explore the legal position of the Labor Court of the 8th Region and theiropiniononthesubject in question. In ordertodevelopthepresentresearch, the use of doctrinairetexts, articles of legal journals, relevantnationallegislation and relevantlaw cases onthesubjectunderstudy, wasdemanded. Thus, it isconcludedthatthe labor accidentis a kind of environmentalpollution. Whenintangibleassets are injured, theemployeedeservestoberepairedatany time, for notonlyhishealthisharmed, butalsotheworker and themembers of thisfamily´shumandignityisaffected. Thisisthefoundation of theRepublic of Brazil,essential for a mantohavequality of life.